Fabrication of Bulk Heterojunction Polymer Solar Cells - Rosa, Erlyta Septa; Shobih, - (LIPI Press, 2014)
In the present work, we used blends of MDMO -PPV [poly(2-methoxy-5-(3,7-dimethyloctyloxy)-1,4-phenylene vinylene)] together with the soluble fullerene C60 derivative PCBM [6,6 phenyl C61-butyric acid methyl ester] as an active layer for bulk heterojunction solar cells. Here, we used a spin coating to deposit a thin and smooth active layer from chlorobenzene solution. An 100 nm thick film of a water solution poly(ethylene dioxythiophene) doped with polystyrene sulphonic acid (PEDOT:PSS) was first spin coated onto an indium tin oxide (ITO)/glass substrate. The PEDOT:PSS layer was then dried in a vacuum oven for 60 minutes at 120C. The active layer, consisting of a blend of the MDMO-PPV and PCBM was then deposited onto the PEDOT:PSS layer from a chlorobenzene solution using spin coating technique. For the cathode, an 134 nm thin film of aluminum was resulted from a thermal evaporation process onto the active layer through a shadow mask to define an active device area of 2,6 cm2. For characterization, the devices was illuminated by a xenon lamp at the intensity of 27 mW/cm2. The temperature ofthe device during characterization was approximately 25C. The device gave an open-circuit voltage of 0.979 volt, a short-circuit current of 0.059 mA, a fill factor of 0.730, and a power conversion efficiency of 0.06%.